2009
DOI: 10.1111/j.1349-7006.2009.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive telomere length and gastric cancer risk: Case‐control analysis in Chinese Han population

Abstract: The shortening of telomeres may result in chromosome instability and thus promote tumorigenesis. Previous studies have demonstrated clear involvement of telomere shortening in the carcinogenesis of several malignancies. However, the association between constitutive telomere shortening and gastric cancer development has yet to be established. Therefore, in the present study, we measured average telomere length using quantitative real-time PCR in peripheral blood lymphocytes from a gastric cancer (GC) case-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 39 publications
1
63
2
Order By: Relevance
“…Comparable results were found with a similar risk (OR 2.14; 95% CI, 1.52-2.93) though smoking potentiated rather than minimized the risk for gastric cancer in this Chinese Han study population [99]. …”
Section: The Gi Tract Cancers Telomeres and Telomere Maintenance Mementioning
confidence: 58%
“…Comparable results were found with a similar risk (OR 2.14; 95% CI, 1.52-2.93) though smoking potentiated rather than minimized the risk for gastric cancer in this Chinese Han study population [99]. …”
Section: The Gi Tract Cancers Telomeres and Telomere Maintenance Mementioning
confidence: 58%
“…Shortened TL in T2DM subjects has previously been observed in Afro-Caribbeans [14], Arabs [15], and Caucasian subjects [17]. Information regarding TL and T2DM among South Asians is scarce, although in this population shortened TL has been observed for other age-related diseases, especially in vascular diseases (coronary artery disease) and hypertension, and cancer [13, 23, 24]. We observed that non-T2DM male subjects had, on average, shorter TL than non-T2DM females, confirming gender dimorphism which was also observed in other ethnic groups (Europeans, Japanese, as well as Arab children) [2527].…”
Section: Discussionmentioning
confidence: 87%
“…The OR for gastric cancer for subjects with the shortest compared to the longest TL quartile was 2.04 (95%CI 2.01 – 4.79, P trend <0.001) (17). Another gastric cancer case-control study (396 cases, 378 controls) presented a significantly increased risk (OR=3.12, 95%CI 2.01 – 4.79, P trend <0.001) in individuals with shortest TL (21). The interbatch CV was 8.1%.…”
Section: Resultsmentioning
confidence: 98%